2010
DOI: 10.1177/0333102410370873
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical pharmacological profile of the selective 5-HT1F receptor agonist lasmiditan

Abstract: Lasmiditan presents a unique pyridinoyl-piperidine scaffold not found in any other antimigraine class. Its chemical structure and pharmacological profile clearly distinguish it from the triptans. The potency and selectivity of lasmiditan make it ideally suited to definitively test the involvement of 5-HT(1F) receptors in migraine headache therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
180
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(193 citation statements)
references
References 29 publications
4
180
0
3
Order By: Relevance
“…Previous studies have reported only a few exceptions to this pharmacological overlap; these ligands are: sumatriptan (46) (Adham et al, 1993) (Nelson et al, 2010). All five drugs have substantially higher affinity at 5-HT 1F receptors versus 5-HT 1E receptors.…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies have reported only a few exceptions to this pharmacological overlap; these ligands are: sumatriptan (46) (Adham et al, 1993) (Nelson et al, 2010). All five drugs have substantially higher affinity at 5-HT 1F receptors versus 5-HT 1E receptors.…”
Section: Discussionmentioning
confidence: 91%
“…The substance does not cause constriction of the saphenous vein of the rabbit in concentrations up to 10 Ϫ4 M. COL-144 also inhibits stimulus-induced c-fos expression in the trigeminal nucleus caudalis of the rat and reduces dural plasma protein extravasation in a standard experimental setup in experimental animals 1 h after oral dosing. 45 The efficacy and an improved tolerability of COL-144 in migraine headaches was demonstrated in a first placebo-controlled study. The study involved 130 patients who were not on prophylaxis and who had moderate to severe migraine headaches.…”
Section: -Ht 1f Receptor Agonists In Migrainementioning
confidence: 99%
“…44 The latest synthesized 5-HT 1F receptor agonist that has been proposed to be effective in migraine is COL-144. 45 Some of these substances have been tested in experimental migraine models.…”
Section: Ly344864mentioning
confidence: 99%
“…For 5-HT 1F receptor agonists it has Table 1. Binding affinity of lasmiditan (n > 5) at human 5-HT receptors [Nelson et al 2010]; Ki (nM). Johnson et al 1997].…”
Section: -Ht 1f Receptor Agonistsmentioning
confidence: 99%